2020
DOI: 10.3390/coatings10100913
|View full text |Cite
|
Sign up to set email alerts
|

SiO2/Ladder-Like Polysilsesquioxanes Nanocomposite Coatings: Playing with the Hybrid Interface for Tuning Thermal Properties and Wettability

Abstract: The present study explores the exploitation of ladder-like polysilsesquioxanes (PSQs) bearing reactive functional groups in conjunction with SiO2 nanoparticles (NPs) to produce UV-curable nanocomposite coatings with increased hydrophobicity and good thermal resistance. In detail, a medium degree regular ladder-like structured poly (methacryloxypropyl) silsesquioxane (LPMASQ) and silica NPs, either naked or functionalized with a methacrylsilane (SiO2@TMMS), were blended and then irradiated in the form of a film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 75 publications
(101 reference statements)
4
18
1
Order By: Relevance
“…The undoped and lanthanide-doped LPGSQ64 films were analyzed by FT-IR spectroscopy before and after curing at 180 °C for 8 h. The as-prepared films with dopants showed absorption peaks not native to the LPGSQ64 film at the wavenumbers from 1632–1634 and 1275–1277 cm −1 ( Figure 5 ), which correspond to the nitrate stretching modes [ 36 ]. The peaks from 1590–1600 cm −1 , interpreted as C=C bonds from the phenyl group [ 7 ], were observed in both undoped and doped films, indicating the inclusion of the phenyl group in the LPGSQ polymer. When cured films were compared, it was seen that the intensity of the phenyl peak at 1600 cm −1 decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The undoped and lanthanide-doped LPGSQ64 films were analyzed by FT-IR spectroscopy before and after curing at 180 °C for 8 h. The as-prepared films with dopants showed absorption peaks not native to the LPGSQ64 film at the wavenumbers from 1632–1634 and 1275–1277 cm −1 ( Figure 5 ), which correspond to the nitrate stretching modes [ 36 ]. The peaks from 1590–1600 cm −1 , interpreted as C=C bonds from the phenyl group [ 7 ], were observed in both undoped and doped films, indicating the inclusion of the phenyl group in the LPGSQ polymer. When cured films were compared, it was seen that the intensity of the phenyl peak at 1600 cm −1 decreased.…”
Section: Resultsmentioning
confidence: 99%
“…For example, an LPSQ composite with Al 2 O 3 demonstrated an improved epoxy conversion rate and wear resistance applicable for deformable display windows [ 6 ]. Similarly, adding SiO 2 nanoparticles to LPSQs increased hydrophobicity and thermal resistance for UV-curable coatings [ 7 ]. ZnO-incorporated LPSQs were also reported for transparent and luminescent optoelectronic devices owing to their optical transparency feature and superior thermal properties of LPSQs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The band at 973 cm -1 confirms the existence of Si–OH stretching vibration [ 37 ]. The wide absorption band around 3600–3200 cm -1 is attributable to the stretching of the OH groups from the physically absorbed water [ 38 ]. It has been shown that the 20 nm SiO 2 NP surfaces used in this study are very clean without any organic material.…”
Section: Resultsmentioning
confidence: 99%
“…SiO 2 @Al 2 O 3 binary filler was functionalized with TMSPM following a modified procedure present in the literature. 37 In detail, SiO 2 @Al 2 O 3 binary filler (ca. 1.0 g) is dispersed inside a round bottom flask in 24 mL of toluene by sonication for 15 min.…”
Section: Surface Functionalization Of the Sio 2 @Al 2 O 3 Binary Fillermentioning
confidence: 99%